Faktor penagihan dadah dalam kalangan penagih dadah wanita di PUSPEN Bachok, Penjara Kajang dan Pusat Khidmat Agensi Antidadah Kebangsaan (PKAADK) Kuala Lumpur - Ahmad, Jamaludin; Shafii, Nor Asida; Sulaiman, Tajul Aripin (Agensi Antidadah Kebangsaan, 2009)
This study is aimed to examine the contributing factors of drug addiction among female addicts and the comparison between the contributing factors which involves three organizations, namely Narcotics Addiction Recovery Center (PUSPEN) Bachok, Kelantan, Kajang Prison, Selangor and National Antidrug Service Agency (PKAADK) Kuala Lumpur. A total of 99 subjects were interviewed individually and in focus group (6–10 individuals in each group). The study involved all the subjects in the Narcotics Addiction Recovery Center (PUSPEN) Bachok, Kelantan (75 individuals), 22 randomly selected subjects from the Kajang Prison, Selangor and 2 voluntary subjects from the PKAADK Kuala Lumpur. The research findings showed that the main contributing factor of drug addiction among female addicts is themselves (36.25%), followed by family (13.06%), peers (12.86%), marriage (12.28%), education (6.62%), materials (5.65%), environment (4.87%), by force (2.14%) and mass media (1.16%). The research findings also indicated that all the three organizations involved stated that individual themselves is the main contributing factor of drug addiction among female addicts. Based on the research findings, several recommendations were made specifically for the National Antidrug Agency (NADA).